Developments in understanding and applying prebiotics in research and practice—an ISAPP conference paper - Sarbini, Shahrul Razid (John Wiley and Sons Inc, 2020)
The concept of using specific dietary components to selectively modulate the gut microbiota to confer a health benefit, defined as prebiotics, originated in 1995. In 2018, a group of scientists met at the International Scientific Association for Probiotics and Prebiotics annual meeting in Singapore to discuss advances in the prebiotic field, focussing on issues affecting functionality, research methodology and geographical differences. The discussion ranged from examining scientific literature supporting the efficacy of established prebiotics, to the prospects for establishing health benefits associated with novel compounds, isolated from different sources. While many promising candidate prebiotics from across the globe have been highlighted in preliminary research, there are a limited number with both demonstrated mechanism of action and defined health benefits as required to meet the prebiotic definition. Prebiotics are part of a food industry with increasing market sales, yet there are great disparities in regulations in different countries. Identification and commercialization of new prebiotics with unique health benefits means that regulation must improve and remain up‐to‐date so as not to risk stifling research with potential health benefits for humans and other animals. This summary of the workshop discussions indicates potential avenues for expanding the range of prebiotic substrates, delivery methods to enhance health benefits for the end consumer and guidance to better elucidate their activities in human studies.